Austerity and Distributional Policy - Matteo Alpino; Zareh Asatryan; Sebastian Blesse; Nils Wehrhöfer (Center for Economic Studies and Ifo Institute (CESifo), 2020)
What are the effects of austerity on distributional policy? We exploit the autonomy of Italian municipalities in setting non-linear income taxes and the exogenous introduction of a fiscal rule to show that austerity increases tax progressivity. Consistent with this evidence, we find that in a panel of countries austerity correlates with higher marginal tax rates on top, but not on average earners. The increase in progressivity in Italy is driven by mayors having college-degree or working in high-skill occupations, while less-educated or lower-skilled mayors raise taxes uniformly. In the first post-reform election, mayors of former type have higher reelection odds.
Keywords: D78; H24; H70; 330; austerity; fiscal rules; non-linear income taxation; difference-in-discontinuity